Comparative Scanning Electron Microscopic Study of the Marginal Adaptation of Four Root-End Filling Materials in Presence and Absence of Blood - Behnam Bolhari; Kazem Ashofteh Yazdi; Farnood Sharifi; Salma Pirmoazen (Tehran University of Medical Sciences, 2015)
Objectives: The aim of this study was to evaluate marginal adaptation of mineral trioxide aggregate (MTA), calcium enriched mixture (CEM) cement, Biodentine and BioAggregate in presence of normal saline and human blood. Materials and Methods: In this in-vitro experimental study, 80 extracted single-rooted human teeth were instrumented and filled with gutta-percha. After resect- ing the root-end, apical cavity preparation was done and the teeth were randomly divided into 4 groups (N=20)(a total of 8 subgroups). Root-end filling materials were placed in 3mm root-end cavities prepared ultrasonically. Half the specimens in each group were exposed to normal saline and the other half to fresh whole human blood. After 4 days, epoxy resin replicas of the apical portion of samples were fabricated and scanning electron microscopy (SEM) analysis was performed to find gaps in the adaptation of the root-end filling materials at their interface with dentin. The Kruskal-Wallis and Mann-Whitney tests were used for statistical analysis of data with P<0.05 as the limit of significance. Results: There were no significant differences in marginal adaptation of the 8 tested groups (P>0.05). Conclusion: Based on the results, blood contamination does not affect the mar- ginal adaptation of MTA, CEM cement, Biodentine or BioAggregate .